2011
DOI: 10.1002/bies.201000136
|View full text |Cite
|
Sign up to set email alerts
|

Growing muscle has different sarcolemmal properties from adult muscle: A proposal with scientific and clinical implications

Abstract: We hypothesise that the sarcolemma of an actively growing myofibre has different properties to the sarcolemma of a mature adult myofibre. Such fundamentally different properties have clinical consequences for the onset, and potential therapeutic targets, of various skeletal muscle diseases that first manifest either during childhood (e.g. Duchenne muscular dystrophy, DMD) or after cessation of the main growth phase (e.g. dysferlinopathies). These characteristics are also relevant to the selection of both tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 80 publications
0
26
0
Order By: Relevance
“…It is conceivable that the smaller diameter of EOM myofibers indeed entails a shorter period of myofiber enlargement by myonuclear accretion. Human studies have shown that EOM myofibers attain maximal diameter by ~12 year of age, while limb and body muscles reach their maximal myofiber diameter ~20 years of age (Grounds and Shavlakadze, 2011). Myofiber growth by nuclear accretion is known to cease earlier than the subsequent growth by cytoplasmic enlargement; e.g., in the mouse LIMB (EDL muscle) myonuclear addition occurs until 3 weeks of age while growth by volume continues even at 8 weeks of age (White et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…It is conceivable that the smaller diameter of EOM myofibers indeed entails a shorter period of myofiber enlargement by myonuclear accretion. Human studies have shown that EOM myofibers attain maximal diameter by ~12 year of age, while limb and body muscles reach their maximal myofiber diameter ~20 years of age (Grounds and Shavlakadze, 2011). Myofiber growth by nuclear accretion is known to cease earlier than the subsequent growth by cytoplasmic enlargement; e.g., in the mouse LIMB (EDL muscle) myonuclear addition occurs until 3 weeks of age while growth by volume continues even at 8 weeks of age (White et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…During postnatal growth, the dynamic properties of the sarcolemma are altered to accommodate myoblast fusion (Blondelle et al, 2015), and growing and mature myofibres differ in their response to growth stimuli (Grounds and Shavlakadze, 2011). This is exemplified by the differing effects of IGF on hypertrophic signalling in skeletal muscle depending on the stage of myofibre maturation; IGF1 is a potent stimulator of hypertrophy, but acts mainly on growing muscle, with a lesser effect seen on normal, mature myofibres (Shavlakadze et al, 2010).…”
Section: Expression Levels Of Mrnas Coding For Proteinsmentioning
confidence: 99%
“…Pax3- and Pax7-expressing cells within the central dermomyotome give rise to both the muscle satellite cells and the embryonic muscle progenitors, which begin differentiation after activation of the myogenic determination genes— Myf5 and MyoD [88]. However, experiments with Pax7 null mice reveal that Pax7 is not necessary for muscle differentiation since prenatal development of knockout mice is normal with the exception of satellite cells which are progressively lost [201, 202].…”
Section: Prenatal Myogenesis and Its Regulatory Mechanismsmentioning
confidence: 99%
“…Satellite cells originate from a population of undifferentiated stem cells in the embryonic dermomyotome [88]. All satellite cells in limb muscle originate from Pax3 + cells of the hypaxial dermomyotome [213].…”
Section: Regulation Of Prenatal Satellite Cells Development Maintenamentioning
confidence: 99%